The Impact of Spiritual Well Being on Self Concept Clarity and Emotional Intelligence Among Adults - Sharanya Sajwan; Smriti R. Sethi (International Journal of Education Sciences, 2025)
Spiritual well-being (SWB) plays a vital role in shaping psychological resilience, emotional regulation, and self- awareness. This study examines the impact of spiritual well-being (SWB) on self-concept clarity (SCC) and emotional intelligence (EI) in adults aged 20-40, while also exploring age and gender differences. SWB, defined as a sense of purpose, inner harmony, and connectedness, influences psychological resilience and emotional regulation. Using the Spiritual Well-Being Scale (SWBS), Self-Concept Clarity Scale (SCCS), and Emotional Intelligence Scale (EIS), correlation and regression analyses reveal significant positive associations. SWB predicts SCC (B = 0.199, p = 0.003, R² = 0.141) and EI (B = 0.208, p = 0.038, R² = 0.072), with a stronger effect on SCC, suggesting that individuals with higher SWB have a clearer sense of self and better emotional regulation .Age-related differences indicate that older adults (31-40) report higher SWB and SCC than younger adults (20-30), supporting the notion that spirituality becomes a stronger psychological resource over time. However, gender differences in the relationship between SWB, SCC, and EI are not statistically significant, suggesting that the influence of spirituality operates similarly across genders. These findings emphasize the interconnected nature of spirituality, identity clarity, and emotional regulation, underscoring SWB as a foundational factor in psychological resilience. Enhancing SWB can lead to greater self-understanding, emotional balance, and overall mental well-being. Future should explore causal mechanisms, cultural variations, and longitudinal effects to further understand how SWB influences identity development and EI over time. This research has practical implications for mental health interventions, suggesting that incorporating spiritual practices could strengthen self-identity and emotional stability. Mental health professionals, educators, and wellness programs may benefit from integrating spiritual techniques to foster resilience, emotional regulation, and a sense of purpose, ultimately supporting a more balanced and fulfilling life across adulthood.
Keywords: Emotional intelligence; Meditation; Mental health; Spiritual well-being; age differences; emotional regulation; emotional stability; mindfulness; psychological resilience; self-awareness; self-concept clarity; spirituality